Desertihabitans aurantiacus gen. nov., sp. nov., a novel member of the family Propionibacteriaceae. Issue 8 (6th June 2019) - Sun, Ye; Wang, Hao; Zhang, Tao; Liu, Wei-Hong; Liu, Hong-Yu; Yu, Li-Yan; Zhang, Yu-Qin
Abstract : The taxonomic position of an actinobacterium isolated from a desert soil sample collected from Badain Jaran Desert, designated as CPCC 204711 T, was established using a polyphasic approach. Cells of the isolate were Gram-staining-positive, aerobic, non-motile cocci. Good growth was observed at 28 °C (range 20–40 °C), pH 7.0 (range pH 6.0–8.0) and 0–1 % NaCl concentration (range 0–5 %, w/v). Galactose, arabinose and ribose were detected as the sugar compositions in the whole cell hydrolysates. The peptidoglycan type was A3gamma (ll -Dpm-Gly). MK-9(H4 ) was detected as the predominant menaquinone, and diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, several unidentified glycolipids, and one unidentified amino-glycolipid were detected as the major polar lipids. The predominant fatty acid was anteiso -C15 : 0 . The genomic DNA G+C content was 73.1 mol%. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain CPCC 204711 T affiliated to the family Propionibacteriaceae, in which the strain formed a distinct phylogenetic lineage next to the genus Mariniluteicoccus, with the highest 16S rRNA gene sequence similarity of 96.0 % to Mariniluteicoccus endophyticus YIM 2617 T . Both phylogenetic analysis and phenotypic characteristics supported that strain CPCC 204711 T represents a novel species of a new genus in the family Propionibacteriaceae, for which the name Desertihabitans aurantiacus gen. nov., sp. nov. is proposed, with CPCC 204711 T (=KCTC 39977 T =DSM 105431 T ) as the type strain.